EVALUASI MANAJEMEN MUTU PROGRAM STUDI PGMI DI STIT SUNAN GIRI BIMA DENGAN MODEL CIPP - Hermawansyah, Hermawansyah; Ibrahim, Misykat Malik; Rasyid, Muhammad Nur Akbar (Prodi PGMI STIT Sunan Giri Bima, 2024)
This study evaluates the quality management of the Elementary School Teacher Education (PGMI) program at STIT Sunan Giri Bima using the CIPP (Context, Input, Process, Product) evaluation model. A descriptive qualitative method with a case study approach was employed. Data were collected through interviews, observations, and documentation. The findings reveal that: 1) The context aspect shows alignment between the institution's vision and mission with modern needs through technology-based curricula and advanced facilities; 2) The input aspect includes qualified lecturers with master's degrees and dual expertise, supported by facilities such as smart classrooms and laboratories; 3) The process aspect demonstrates innovative technology-based learning and active interaction between lecturers and students, including the use of digital media; 4) The product aspect indicates graduates possess both academic and practical competencies relevant to workforce demands, with many alumni contributing to primary education in society. This evaluation highlights the importance of continuous development, including enhancing lecturer competencies and aligning curricula with global demands. The findings are expected to serve as a reference for improving education quality at STIT Sunan Giri Bima and similar institutions, producing high-quality educators capable of competing at national and international levels.